ТИПОМОРФНЫЕ ОСОБЕННОСТИ ЗОЛОТА ИЗ РАЗНОВОЗРАСТНЫХ ОТЛОЖЕНИЙ ЮГО-ВОСТОЧНОЙ ЧАСТИ ОЛЕНЕКСКОГО ПОДНЯТИЯ - Герасимов Б.Б.; Никифорова З.С. (My University, 2005)
As a result of studying typomorphic features of gold from the differently aged gold ore deposits at southeastern part of Olenek uplift (Eiekit river basin), there were, for the first time, distinguished two types of gold. The first type gold is characterized by the high standard of gold particles with the average 0.1-0.16 mm size; it occurs in quartz-carbonate Proterozoic veins, Riphean and Permian gold-bearing intermediate collectors, and it is related basically to the ancient Precambrian sources. The second type gold, represented by the low-intermediate standard particles, with 0.2-0.25 mm average size, occurs, together with the first type one, within the summit pebble beds of the Middle-Late Pleistocene and contemporary alluvium. Presence of the second type gold within deposits not older then the Cenozoic age, its considerable difference, from the first type, by typomorphical features, brings to conclusion of its younger, supplementary sources, probably of Mesozoic age.
Keywords: Cenozoic; Mesozoic; Proterozoic; Permian; Cambrian; Pleistocene; Precambrian; Riphean; 549.263; Cenozoic; Mesozoic; Precambrian::Proterozoic; Paleozoic::Permian; Paleozoic::Cambrian; Cenozoic::Quaternary::Pleistocene; Precambrian; Precambrian::Proterozoic::Riphean